2017
DOI: 10.1111/cid.12487
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement and restoration in the anterior maxilla: Tissue dimensional changes after 2‐5 year follow up

Abstract: In addition to a favorable implant success rate and peri-implant bony response, the soft tissue levels and overall aesthetics around single immediately placed and restored implants can also be maintained in the mid-long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 33 publications
7
81
1
8
Order By: Relevance
“…Thus, an obvious higher recession value compared with baseline (△ML) was measured. This phenomenon has also been reported by Aoral et al Gingival recession can sometimes be induced purposefully by the prosthodontist to create harmony with the soft tissue level on the contralateral tooth, which may be deemed to have experienced “advanced” recession. Little research is available in terms of the initial gingival level of the failure tooth compared with the contralateral tooth with regard to difficulties in building a proper 3D coordinate to determine the horizontal line.…”
Section: Discussionsupporting
confidence: 61%
“…Thus, an obvious higher recession value compared with baseline (△ML) was measured. This phenomenon has also been reported by Aoral et al Gingival recession can sometimes be induced purposefully by the prosthodontist to create harmony with the soft tissue level on the contralateral tooth, which may be deemed to have experienced “advanced” recession. Little research is available in terms of the initial gingival level of the failure tooth compared with the contralateral tooth with regard to difficulties in building a proper 3D coordinate to determine the horizontal line.…”
Section: Discussionsupporting
confidence: 61%
“…Type 2 placement of Straumann ® bone level implants has also been reported to exhibit minimal marginal bone changes (0.18 mm) after 3 years of loading . Comparable results have also been reported with AstraTech ® implants . A systematic review analyzing Type 1–4 implant placements in the esthetic zone reported a mean marginal bone loss of 0.20 mm [95% CI: (0.034‐0.36)] during the first year after installation of the definitive crown …”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, although the PES index attempts to provide an objective measure of esthetic outcome, it is nevertheless open to individual interpretation and the outcomes of certain parameters may be differently evaluated by different investigators, resulting in the contradictory reports. The PES/WES scores were determined from photographs, consistent with other studies reporting on this parameter . However, not carrying out this evaluation directly on the patient may be considered a limitation, and future studies could address whether there are differences in the outcomes between esthetic assessments undertaken from photographs/models compared to “live” evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…The overall dimensional reduction of the labial bone was 1.21 ± 1.44 mm for vertical bone resorption and 0.65 ± 0.61 mm for horizontal bone resorption at 1 year postoperatively. Similar results have been reported in a systematic review by Clementini M, with a slightly higher vertical loss (0.79 mm) and lower horizontal loss (1.02 mm), as well as in other tissue alteration results from studies about IIPP …”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported in a systematic review by Clementini M, with a slightly higher vertical loss (0.79 mm) and lower horizontal loss (1.02 mm), 26 as well as in other tissue alteration results from studies about IIPP. 13,[26][27][28][29][30][31][32] The thickness of the labial plate influences its dimensional resorption rate in IIPP. Koh et al, stated the strong correlation between labial plates with a thickness less than 2 mm and horizontal bone loss.…”
Section: Esthetic Assessmentmentioning
confidence: 99%